1983
DOI: 10.2307/2273668
|View full text |Cite
|
Sign up to set email alerts
|

On a generalization of Jensen's □κ, and strategic closure of partial orders

Abstract: Link to this article: http://journals.cambridge.org/abstract_S0022481200037415How to cite this article: Dan Velleman (1983). On a generalization of Jensen's □ κ , and strategic closure of partial orders . Introduction.It is well known that many statements provable from combinatorial principles true in the constructible universe L can also be shown to be consistent with ZFC by forcing. Recent work by Shelah and Stanley [4] and the author [5] has clarified the relationship between the axiom of constructibility a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
6
0

Year Published

1986
1986
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…As for G n -type games, Velleman [11] has shown that for any infinite cardinal K, every cr-closed, (K + 1)-strategically closed poset is K + -strategically closed if and only if D K holds. Ishiu and Yoshinobu [5] have shown that the condition 'a-closed' can be dropped in Velleman's result.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…As for G n -type games, Velleman [11] has shown that for any infinite cardinal K, every cr-closed, (K + 1)-strategically closed poset is K + -strategically closed if and only if D K holds. Ishiu and Yoshinobu [5] have shown that the condition 'a-closed' can be dropped in Velleman's result.…”
mentioning
confidence: 99%
“…Note that D w is provable in ZFC. D K can be considered as a property of K + , rather than of K. From this point of view Velleman [11] generalized the notion of square principles, enabling us to mention its 'limit cardinal analogue'. DEFINITION 2.2.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However we know that this may fail in the above models. Namely, using a result of Laver it was observed by Velleman in [16] that it is consistent that there is a supercompact cardinal K and a set S £ K + such that {a < K + |cof a = K} £ S and D s holds. Now both the Levy collapse of K and the standard poset forcing PFA are K-CC, SO the class of ordinals of cofinality K remains the same in the extension and our sequence is still a Ds sequence.…”
mentioning
confidence: 99%
“…The following is a slight modification of the partial order for adding a D W2 sequence with countable conditions, see e.g. Velleman [16]. EXAMPLE Now it is straightforward to check that 3P is tr-closed and, if CH holds, also satisfies the K 2 -cc.…”
mentioning
confidence: 99%